Structural Imbalances in Public Financial Management in Libya: Challenges and Pathways to Reform (Comprehensive Journal of Science, 2026)
This research, will explore the structural imbalances in public financial management in Libya, focusing on the absence of a unified national budget and its implications for the country’s economic stability and sustainable development. This study will analyze the historical context of political fragmentation and conflict that has led to significant institutional weaknesses and a lack of transparency, hindering effective financial governance. Through a detailed examination of fragmented fiscal decision-making, This study will highlight how inefficiencies and inconsistencies in financial policies exacerbate governance challenges, including corruption and limited accountability. This study will argue that these issues contribute to economic disparities and vulnerabilities in revenue management, necessitating comprehensive reforms. The research emphasizes the urgent need for integrating financial policies, enhancing governance through transparency and accountability, and strategic spending that addresses developmental priorities. The findings underscore the critical pathways to reform that can foster a stable and sustainable economic environment in Libya.
Keywords: Public Financial Management, Libya, Structural Imbalances, Economic Stability, Governance Reforms